Optimalisasi Kinerja Pompa Minyak Lumas Untuk Mencegah Penurunan Tekanan Pada Generator Engine Type Daihatsu di MV. Great Venture - Bagus Viky Satriatama; ngatmin ngatmin; Wahyu Ari Putranto; Arif Rakhman Suharso; Noviarianto Noviarianto (Jurnal Maritim Polimarin, 2026)
The lubrication system serves not only to lubricate moving and stationary parts but also plays a role in cooling the engine. This study aims to identify the factors causing a rise in lubricating oil temperature and a drop in pressure within the diesel generator's auxiliary engine. The research was conducted aboard the MV. Great Venture, owned by Wah Kong. A qualitative descriptive method was employed, utilizing interviews with the Third Engineer. The findings indicate that the rise in temperature and drop in lubricating oil pressure were caused by the clogging of the oil pump filter due to sealant debris originating from the L.O. cooler. The solution to this issue is to perform routine maintenance on the generator engine in accordance with the Planned Maintenance System (PMS).